O currículo e a educação em Ciências na educação infantil : trajetórias construídas e em construção das propostas curriculares na Secretaria Municiapl de Educação de Manaus - Prado, Helane Mary de Oliveira (2018)
The present work describes the historical trajectory of the construction of the curricular proposals of Early Childhood Education in our country, as well as the pedagogical proposals elaborated by the Municipal Education Department of Manaus (SEMED), highlighting children's conceptions, development and approach given to Science Education through the themes of the natural sciences. The decade of 1990 was marked by a growing production of normative documents that aimed to implement the advances that occurred, in what refers to the directions that was intended to give to Infant Education in Brazil. Thus, in order to contextualize the builtup trajectories of pedagogical curricular proposals for Early Childhood Education, the 1990s are taken as a starting point until the year 2016. This is a research based on documental analysis and on a qualitative approach that reveals the importance of understanding today's curriculum as a movement that involves the various actions lived inside and outside educational institutions. As well, it highlights the fact that children are considered citizens with rights, which required the reorganization of the legal precepts of education in the country, the preparation of guiding documents that established criteria for the functioning of educational institutions, frequented by infants and children covering their physical structure, the elaboration of the pedagogical proposal and the pedagogical work of the teachers directed to their formation.The curricular-pedagogical proposals elaborated, recognize the care and education as inseparable actions, mention the specifics of children, the importance of promoting activities that challenge them to think, experiment and make new discoveries. However, they do not involve science subjects as much as they do not relate them to a science education, which we point out as appropriate to foster the integral development of young children. Keywords: Curriculum. Child Education. Education in Sciences